2016
DOI: 10.1080/02656736.2016.1239842
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous microwave ablation of 5-6 cm unresectable hepatocellular carcinoma: local efficacy and long-term outcomes

Abstract: MWA is safe and effective for the treatment of selected large HCCs, and provides an alternative treatment option for patients with unresectable HCCs. Furthermore, the favourable local efficacy of MWA could potentially improve long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…One such strategy is TACE plus MWA. Previous studies reported that TACE plus MWA is much more effective than conventional TACE in patients with large solitary HCCs ( 12 13 ). However, to the best of our knowledge, no study has yet analyzed outcomes after TACE plus MWA in patients with large solitary and multinodular (not more than 10 tumors) HCCs.…”
Section: Introductionmentioning
confidence: 97%
“…One such strategy is TACE plus MWA. Previous studies reported that TACE plus MWA is much more effective than conventional TACE in patients with large solitary HCCs ( 12 13 ). However, to the best of our knowledge, no study has yet analyzed outcomes after TACE plus MWA in patients with large solitary and multinodular (not more than 10 tumors) HCCs.…”
Section: Introductionmentioning
confidence: 97%
“…According to systematic reviews and meta-analysis, percutaneous radiofrequency and microwave ablation demonstrated similar efficacy for the treatment of HCC, but with an apparent superiority of MWA in larger neoplasms [32]. The superiority of microwave ablation in large diameter HCC is reported in most literature studies [33][34][35]. Moreover, various studies comparing the specific microwave system used in the present study to low-frequency microwave generators reported significantly higher ablation volumes, longer time to progression and lower progression rates for high-power/ high-frequency systems [36].…”
Section: Discussionmentioning
confidence: 99%
“…As it is shown in the results, large tumors (tumor diameter >50 mm) have less chance of success and more chance of recurrence compared to smaller ones. In another study which was focused on MWA of large HCC tumors (5–6 cm) in 82 patients, local efficacy and long-term outcomes were investigated [ 48 ]. A Qinghai FORSEA MWA system with a 14-gauge cooled shaft antenna was used in this study.…”
Section: Percutaneous Microwave Ablation Of Liver Tumorsmentioning
confidence: 99%
“…As seen throughout these studies and mentioned previously, tumors < 3cm appear to have the best rates for overall survival. Recommended tumor classification for MWA treatment can be given by ECOG level (0–2), Barcelona Clinic Liver Cancer (BCLA 0 to A), and/or Child-Pugh score (A to B) [ 47 , 48 , 49 , 88 ]. Depending on tumor location (within the tumor or on the surface), MWA would be preferable, but not limited, to tumors buried within the liver [ 91 ].…”
Section: Percutaneous Microwave Ablation Of Liver Tumorsmentioning
confidence: 99%
See 1 more Smart Citation